2015
DOI: 10.1177/0363546515584760
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Slow Resistance Versus Eccentric Training as Treatment for Achilles Tendinopathy

Abstract: The results of this study show that both traditional ECC and HSR yield positive, equally good, lasting clinical results in patients with Achilles tendinopathy and that the latter tends to be associated with greater patient satisfaction after 12 weeks but not after 52 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
319
5
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(358 citation statements)
references
References 46 publications
20
319
5
14
Order By: Relevance
“…We selected the eccentric heel drop as it remains an integral part of Achilles tendon rehabilitation (Beyer et al, 2015;Habets and van Cingel, 2015;Kjaer and Heinemeier, 2014), induces high tendon strains (∼8.5%; Jeong et al, 2014) and has been shown to affect immediate changes in mechanical (Obst et al, 2015) and 2D morphological (Grigg et al, 2009) properties of the Achilles free tendon in healthy adults. We expected that transverse morphology and strain (CSA, AP diameter and ML diameter) of the Achilles free tendon would be altered immediately following exercise and correlated to the corresponding change in longitudinal strain.…”
Section: Introductionmentioning
confidence: 99%
“…We selected the eccentric heel drop as it remains an integral part of Achilles tendon rehabilitation (Beyer et al, 2015;Habets and van Cingel, 2015;Kjaer and Heinemeier, 2014), induces high tendon strains (∼8.5%; Jeong et al, 2014) and has been shown to affect immediate changes in mechanical (Obst et al, 2015) and 2D morphological (Grigg et al, 2009) properties of the Achilles free tendon in healthy adults. We expected that transverse morphology and strain (CSA, AP diameter and ML diameter) of the Achilles free tendon would be altered immediately following exercise and correlated to the corresponding change in longitudinal strain.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms may become severe without adequate rest and treatment. Systemic nonsteroidal anti-inflammatory drugs, 12 transcutaneous electrical nerve stimulation, eccentric training, 4,5 heavy slow resistance training, 13 laser, ultrasound, 12 and massage have been described as potentially useful methods. As mentioned for interventional choice, radiofrequency therapies, plateletrich plasma injections, local glucocorticosteroid injections, or surgery 12 are chosen for chronic cases.…”
Section: Discussionmentioning
confidence: 99%
“…Malliaras and his colleagues [16] concluded that clinicians should consider eccentric -concentric loading alongside or instead of eccentric loading in Achilles and patellar tendinopathy. A Heavy Slow Resistance (HSR) program is recommended in the management of lower limb tendinopathy [26,27]. The HSR program was produced equivalent pain and function improvement (VISA) than the Alfredson eccentric program, but significantly better patient satisfaction at six month follow -up.…”
Section: Discussionmentioning
confidence: 99%